2015
DOI: 10.1093/mnras/stv1798
|View full text |Cite
|
Sign up to set email alerts
|

NGC 6845: metallicity gradients and star formation in a complex compact group

Abstract: We have obtained Gemini/GMOS spectra of 28 regions located across the interacting group NGC 6845, spanning from the inner regions of the four major galaxies (NGC 6845A, B, C, D) to the tidal tails of NGC 6845A. All regions in the tails are starforming objects with ages younger than 10 Myr. We derived the gas-phase metallicity gradients across NGC 6845A and its two tails and we find that these are shallower than those for isolated galaxies. NGC 6845A has a gas-phase oxygen central metallicity of 12+log(O/H)∼8.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
4
2
0
Order By: Relevance
“…This gas mixing process has been observed in interacting galaxies (e.g. Kewley et al 2006;Rupke et al 2010;Torres-Flores et al 2014;Rosa et al 2014;Olave-Rojas et al 2015) Numerical simulation predicted the flattening of the metallicity gradient to occurs just after first pericenter passage (Rupke et al 2010;Perez et al 2011) hence the age of interaction stage, about 50 ± 25 Myr after pericenter, that we estimated (Sec 3.6) is a good agreement with this scenario. The presence of the AGN 2011), and thus with the higher fraction seen in close pairs of composite galaxies (i. e. galaxies whose central region is ionized by nuclear activity and massive stars) than in systems.…”
Section: The Effects Of the Interactions On Ngc 2936supporting
confidence: 87%
“…This gas mixing process has been observed in interacting galaxies (e.g. Kewley et al 2006;Rupke et al 2010;Torres-Flores et al 2014;Rosa et al 2014;Olave-Rojas et al 2015) Numerical simulation predicted the flattening of the metallicity gradient to occurs just after first pericenter passage (Rupke et al 2010;Perez et al 2011) hence the age of interaction stage, about 50 ± 25 Myr after pericenter, that we estimated (Sec 3.6) is a good agreement with this scenario. The presence of the AGN 2011), and thus with the higher fraction seen in close pairs of composite galaxies (i. e. galaxies whose central region is ionized by nuclear activity and massive stars) than in systems.…”
Section: The Effects Of the Interactions On Ngc 2936supporting
confidence: 87%
“…The average value for the oxygen abundance for the six regions is 12+log(O/H) ∼ 8.6, which is very similar to typical values for extragalactic Hii regions reported in the literature for other interacting systems (e.g. Werk et al 2010;de Mello et al 2012;Olave-Rojas et al 2015).…”
Section: Oxygen Abundancesupporting
confidence: 85%
“…Thus, these regions are similar to extragalactic Hii regions found in recent or ongoing mergers (e.g. Mendes de Oliveira et al 2001;de Mello et al 2012;Olave-Rojas et al 2015). Torres-Flores et al (2012) found similar objects around the system NGC 2782, an ongoing merging galaxy which shows optical and Hi tidal tails containing several Hii regions.…”
Section: Star Formation Outside Galaxiessupporting
confidence: 73%
“…The distribution of metals in the disks of spiral galaxies has been studied by several authors (Zaritsky et al 1994;van Zee et al 1998;Moustakas et al 2010;Sánchez et al 2014), who have found that most of spiral galaxies show clear chemical gradients, where the central regions are most metal rich than the outskirts. On the other hand, numerous observational studies have found that interacting galaxies have flatter gradients and lower nuclear metallicities than isolated galaxies (Rupke et al 2010b;Kewley et al 2010;Bresolin et al 2012;Rich et al 2012;Rosa et al 2014;Torres-Flores et al 2014;Olave-Rojas et al 2015). Numerical simulations indicate that this drop in nuclear abundances is produced by gas inflows and gas redistributions along the galactic discs, which also produces a general flattening in the metal distribution (Rupke et al 2010a;Montuori et al 2010;Torrey et al 2012).…”
Section: Oxygen Abundance Gradientmentioning
confidence: 94%